#### Answer

$6$

#### Work Step by Step

First solve for the second equation
$2(x - 6) = 3x + 2(2x - 1)$
$2x - 12 = 3x + 4x - 2$
$2x - 12 = 7x - 2$
$-5x = 10$
$x = -2$
Plug $x=-2$ into the first equation
$x^{2}- x$
$(-2)^{2}- (-2)$
$4+2 = 6$

Published by
Pearson

ISBN 10:
0-32178-228-3

ISBN 13:
978-0-32178-228-1

$6$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.